2022
DOI: 10.1155/2022/2923291
|View full text |Cite
|
Sign up to set email alerts
|

UTP14A, DKC1, DDX10, PinX1, and ESF1 Modulate Cardiac Angiogenesis Leading to Obesity-Induced Cardiac Injury

Abstract: Background. This study is aimed at exploring the key genes and the possible mechanism of heart damage caused by obesity. Methods. We analyzed the GSE98226 dataset. Firstly, differentially expressed genes (DEGs) were identified in heart tissues of obese and normal mice. Then, we analyzed DEGs using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis. Thirdly, we constructed a protein-protein interaction (PPI) network and key modules and searched hub genes. Finally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Studies have found that CEACAM1 [237], STAT1 [238], ARG1 [239], TLR4 [240], LRRK2 [241], ABCA1 [242], PTGS2 [243], CYP2D6 [244], JAK2 [245], TLR2 [246], DUSP6 [247], CYP1B1 [248], CCR1 [249], HDAC9 [250], LATS2 [251], IL1RN [252], GCH1 [253], PELI1 [254], EGR1 [255], HIPK3 [256], CCR2 [257], GCLC (glutamate-cysteine ligase catalytic subunit) [258], KLF3 [259], VEGFA (vascular endothelial growth factor A) [260], ITGB1 [261], RASA1 [262], PTPN12 [263], SNRK (SNF related kinase) [264], PRKAR1A [265], LDLR (low density lipoprotein receptor) [266], SIRT1 [267], NOD2 [268], VCAN (versican) [269], TET2 [270], PFKFB2 [271], ZBTB20 [272], MYBL2 [273], PF4 [274], VEGFB (vascular endothelial growth factor B) [275], CCR7 [276], PRDX2 [277], HSPB1 [278], ZNF791 [279], IGFBP4 [280], ESF1 [281], SNHG8 [282], LGALS3 [283] and LGMN (legumain) [284] are altered expression in myocardial infarction. Altered expression of CEACAM1 [176], ACSL1 [285], STAT1 [286], TLR4 [287], ABCA1 [288], TLR5 [183], F2RL1 [289], CYP2D6 [290], PDK4 [291], RNF213 [186], JAK2 [292], TLR8 [189], NOTCH2 [293], CENPJ (centromere protein J) [294], FNIP1 [295], TLR2 [296], KIDINS220 [297], DUSP6 [298], CYP1B1 [299], S1PR3 [300], NCOA2 [301], HDAC9 [302], PELI1 [303], EGR1 [304], HIF1A [305], CCR2 [306], IR...…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that CEACAM1 [237], STAT1 [238], ARG1 [239], TLR4 [240], LRRK2 [241], ABCA1 [242], PTGS2 [243], CYP2D6 [244], JAK2 [245], TLR2 [246], DUSP6 [247], CYP1B1 [248], CCR1 [249], HDAC9 [250], LATS2 [251], IL1RN [252], GCH1 [253], PELI1 [254], EGR1 [255], HIPK3 [256], CCR2 [257], GCLC (glutamate-cysteine ligase catalytic subunit) [258], KLF3 [259], VEGFA (vascular endothelial growth factor A) [260], ITGB1 [261], RASA1 [262], PTPN12 [263], SNRK (SNF related kinase) [264], PRKAR1A [265], LDLR (low density lipoprotein receptor) [266], SIRT1 [267], NOD2 [268], VCAN (versican) [269], TET2 [270], PFKFB2 [271], ZBTB20 [272], MYBL2 [273], PF4 [274], VEGFB (vascular endothelial growth factor B) [275], CCR7 [276], PRDX2 [277], HSPB1 [278], ZNF791 [279], IGFBP4 [280], ESF1 [281], SNHG8 [282], LGALS3 [283] and LGMN (legumain) [284] are altered expression in myocardial infarction. Altered expression of CEACAM1 [176], ACSL1 [285], STAT1 [286], TLR4 [287], ABCA1 [288], TLR5 [183], F2RL1 [289], CYP2D6 [290], PDK4 [291], RNF213 [186], JAK2 [292], TLR8 [189], NOTCH2 [293], CENPJ (centromere protein J) [294], FNIP1 [295], TLR2 [296], KIDINS220 [297], DUSP6 [298], CYP1B1 [299], S1PR3 [300], NCOA2 [301], HDAC9 [302], PELI1 [303], EGR1 [304], HIF1A [305], CCR2 [306], IR...…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics methods were executed following previous literature. 31 Diabetes, Metabolic Syndrome and Obesity 2024:17…”
Section: Screening Of Differentially Expressed Proteins (Deps)mentioning
confidence: 99%
“…By promoting cellular senescence via p16/cyclin D1 pathway, pinX1 suppresses bladder urothelial carcinoma cell proliferation [13]. In recent years, researchers have provided some clues that pinX1 still plays an important role in processes such as inflammatory-related lipopolysaccharide-induced lung injury [14] and lipid metabolism such as obesity-induced cardiac injury [15], nonalcoholic fatty liver disease [16]. PinX1 gene single nucleotide polymorphisms (SNPs) are correlated with serum lipid levels [17].…”
Section: Introductionmentioning
confidence: 99%